Kenya beef records: pt.1: field handbook Pt. 2: data preparation handbook Pt. 3 Computer operation manual - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Field handbook dealing w. cooperative programme carried out by the Kenya Ministry of Agriculture and ILCA, with particular reference to Strengthening the Beef Records of the govt's Livestock Recording Centre; Outlines on beef recording Scheme, data, collection & analysis, data preparation and computer operation.